Mushroom Bulgaria inquinans Modulates Host Immunological Response and Gut Microbiota in Mice - Sang, Hongzhen; Xie, Yu; Su, Xing; Zhang, Mengdi; Zhang, Yijie; Liu, Kun; Wang, Junpeng (Frontiers in Nutrition, 2020)
We aimed to determine the prebiotic impact of Mushroom Bulgaria inquinans (BI) on the host immune response and gut microbiota. Male C57BL/6 mice were fed diet supplemented with 0%, 1% or 2% BI for 4 wks. Compared to mice fed with control diet (0% BI), mice fed with 1% or 2% BI had an increase of T cell proliferation from spleen but such change was not found between 1% and 2% BI treated mice. Also, BI at 2% increased production of IL-2 of splenocytes stimulated with T-cell mitogens, but BI at 1% and 2% did not affect productions of other splenic-T cell cytokines including IL-4, IL-10, and IFN-γ. Interestingly, BI at 1% or 2% inhibited T cell proliferation of mesenteric lymph node (mLN) but this effect was not found between 1% and 2% BI treated mice. Furthermore, BI inhibited the production of IL-2 in anti-CD3/CD28-stimulated T cells from mLN in a dose-dependent manner. Meanwhile, BI at 2%, not 1% inhibited the production of IL-4, IL-10, and IFN-γ of mLN. Since BI at 2%prodced a more significant effect of the immune response, we further used BI at 2% to evaluate the effect of BI on gut microbiota. Of note, BI reduced the diversity of gut microbiota and resulted in an increase of Faecalibaculum and Parabacteroides abundance and the decrease of Allobaculum, Candidatus_Saccharimonas, and Rikenella abundance at the genus level. Finally, the correlation was observed between specific bacteria genera and the productions of T-cell cytokines from mesenteric lymphocytes: Rikenella and Candidatus_Saccharimonas correlated positively with IL-2, IL-4, IL-10, and IFN-γ; Bacteroides and Parabacteroides correlated negatively with IL-2 and IL-4; Faecalibaculum correlated negatively with IFN-γ and IL-4 and Bacteroides, and Bifidobacterium correlated negatively with IFN-γ. The specific role of each intestinal microbiota observed is still unclear, but BI might exert a prebiotic effect on gut microbiota by increasing the abundance of potentially beneficial bacteria (Faecalibaculum). This is helpful for further demonstrating the healthy-promotion mechanism of Bulgaria inquinans.